2015
DOI: 10.1002/2015jd023878
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MODIS Terra radiometric calibration improvements on Collection 6 Deep Blue aerosol products: Validation and Terra/Aqua consistency

Abstract: The Deep Blue (DB) algorithm's primary data product is midvisible aerosol optical depth (AOD). DB applied to Moderate Resolution Imaging Spectroradiometer (MODIS) measurements provides a data record since early 2000 for MODIS Terra and mid‐2002 for MODIS Aqua. In the previous data version (Collection 5, C5), DB production from Terra was halted in 2007 due to sensor degradation; the new Collection 6 (C6) has both improved science algorithms and sensor radiometric calibration. This includes additional calibratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
120
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(125 citation statements)
references
References 61 publications
(102 reference statements)
5
120
0
Order By: Relevance
“…The C6 DT expected error is ±(0.05 + 0.15τ AERONET ) over land and +(0.04 + 0.1τ AERONET ), −(0.02 + 0.1τ AERONET ) over sea relative to the AERONET optical thickness (τ AERONET ) (Levy et al, 2013). The C6 DB expected error is ∼ ±0.03 + 0.2τ MODIS ) relative to the MODIS optical thickness (τ MODIS ) Sayer et al, 2015).…”
Section: Modismentioning
confidence: 85%
See 1 more Smart Citation
“…The C6 DT expected error is ±(0.05 + 0.15τ AERONET ) over land and +(0.04 + 0.1τ AERONET ), −(0.02 + 0.1τ AERONET ) over sea relative to the AERONET optical thickness (τ AERONET ) (Levy et al, 2013). The C6 DB expected error is ∼ ±0.03 + 0.2τ MODIS ) relative to the MODIS optical thickness (τ MODIS ) Sayer et al, 2015).…”
Section: Modismentioning
confidence: 85%
“…Details about these updates in C6 DT and DB data can be found in a number of recent studies (e.g., Levy et al, 2013;Tao et al, 2015;Sayer et al, 2015;Georgoulias et al, 2016). Corrections for polarization, gain and response-versus-scan corrections and detrending for MODIS/Terra degradation have been included in DB but not in DT.…”
Section: Modismentioning
confidence: 99%
“…A challenge in using long-term satellite records to detect change is maintaining consistent instrument performance. Recent literature has discussed MODIS Terra sensor calibration degradation and its impacts on apparent data trends (e.g., Franz et al, 2008;Wang et al, 2012;Lyapustin et al, 2014;Polashenski et al, 2015;Sayer et al, 2015). Specifically related to GrIS trends, a recent work by Polashenski et al (2015) indicated that uncorrected sensor degradation in MODIS Collection 5 (C5) data, particularly on the Terra platform, was contributing significantly to an apparent albedo declining trend over the GrIS and that the albedo trend in large areas of the ice sheet which do not experience melt (the dry snow area) may disappear once Collection 6 (C6) calibrations are applied.…”
Section: Introductionmentioning
confidence: 99%
“…The uncertainty in the AOD (δx C ) from DB is ±(0.03 + 0.23τ) [30] as discussed before. We used the α uncertainty calculated from DT, which is 0.4 [45], since we could not find literature supporting uncertainty of α (δy C ) derived from DB.…”
Section: Uncertainty Estimation and Validationmentioning
confidence: 72%
“…Bilal and Nichol [29] found that DB retrieved AOD performed well compared to AERONET in the national capital region of China on both hazy and clear days, yet tended to overestimate during very polluted days (AOD > 1.5). The level of uncertainty of DB Collection 6 AOD retrievals (QA = 3) is approximately ±(0.03 + 0.23τ) [30], an improvement over Collection 5.1 uncertainty of ±(0.05 + 0.2τ) [31]. In Collection 6, a 'best of' AOD product also exists that combines AOD from DB and DT algorithms to estimate aerosol distribution over densely vegetated areas as well as bright surfaces.…”
Section: Datasets Usedmentioning
confidence: 99%